2021
DOI: 10.48550/arxiv.2108.04810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Khovanov homology and exotic surfaces in the 4-ball

Abstract: We show that the cobordism maps on Khovanov homology can distinguish between exotically knotted smooth surfaces in the 4-ball that are isotopic through ambient homeomorphisms but not ambient diffeomorphisms. Our proof uses a new approach to distinguishing the cobordism maps on Khovanov homology, and we highlight additional applications of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, in [13, section 2.1], it is shown that 𝐷 and 𝐷 ′ are not smoothly isotopic (or even diffeomorphic) rel boundary. (See also [18,Theorem 3.2].) Note that 𝐽 admits a strong inversion 𝜏; a crucial part of the argument in [13] relies on the fact that 𝐷 and 𝐷 ′ are related by the obvious extension of 𝜏 over 𝐵 4 .…”
Section: Applicationsmentioning
confidence: 99%
“…However, in [13, section 2.1], it is shown that 𝐷 and 𝐷 ′ are not smoothly isotopic (or even diffeomorphic) rel boundary. (See also [18,Theorem 3.2].) Note that 𝐽 admits a strong inversion 𝜏; a crucial part of the argument in [13] relies on the fact that 𝐷 and 𝐷 ′ are related by the obvious extension of 𝜏 over 𝐵 4 .…”
Section: Applicationsmentioning
confidence: 99%
“…boundary, including exotic examples [HS21, LS21, SS21]. Moreover, the approach in [HS21] demonstrates the computability of such maps: by carefully choosing a cycle ψ ∈ CKh(L) from the Khovanov chain complex of L, we can control the complexity of calculating the induced chain maps CKh(S 0 )(ψ) and CKh(S 1 )(ψ). Moreover, the calculations in this paper only require a subset of the Morse and Reidemeister induced chain maps (c.f.…”
Section: Obstructions From Khovanov Homologymentioning
confidence: 99%
“…For closed surfaces, this invariant turns out not to be interesting: it vanishes if some component of the surface is not a torus, and otherwise is 2 n if the surface consists of n tori [146,60]. On the other hand, for surfaces with boundary a nontrivial link in S 3 , Khovanov homology does give an interesting invariant [169], even distinguishing some surfaces that are topologically isotopic [64].…”
Section: Applicationsmentioning
confidence: 99%